Comparing Biorefinery Processes at the Early Design Stage Using Large Block Analysis - Trottier, Émanuelle; Myers, Craig; Stuart, Paul (Frontiers in Sustainability, 2022)
The transformation and the diversification of pulp and paper mills through the integration of biorefineries is increasingly considered essential to the future of many sites, however evaluating the risk and return of different process alternatives at the early design stage is challenging. There are many strategies and technologies that should be considered, each of which is typically accompanied by unique risks, as well as high uncertainties in capital and operating costs. The methodology presented in this study called Large Block Analysis (LBA) comprises a systematic approach for addressing these challenges. We describe how LBA is used to obtain relative cost estimates for different technologies having different Technology Readiness Levels (TRLs), and evaluate 6 process/product combinations for adding value to a wood-extracted hemicellulose stream. The cost estimates obtained by the Large Block Analysis method differ from initial estimates (mainly from technology developers) by between 121% and -19% for the fixed capital cost, and between 117% and -17% for the operating cost. The results show that the production of animal feed additives, of xylitol by a variation of the classical chemical process and of furfural were most promising with an internal rate of return above 15% and accompanied by reasonable risk.